On Embedding of Repetitive Meyer Multiple Sets into Model Multiple Sets - Aujogue-, J (Cambridge University Press, 2016)
Model sets are always Meyer sets but the converse is generally not true. In this work we show that for a repetitive Meyer multiple set of with associated dynamical system , the property of being a model multiple set is equivalent to being almost automorphic. We deduce this by showing that a repetitive Meyer multiple set can always be embedded into a repetitive model multiple set having a smaller group of topological eigenvalues. © Cambridge University Press, 2015.